A new recessive syndrome of unusual facies, digital abnormalities, and ichthyosis. Issue 5 (May 1989) - Clayton-Smith, J; Donnai, D
Abstract : Two sibs with a similar pattern of unusual facial features, limb malformations, and postnatal onset of ichthyosis are reported. The parents are first cousins and neither shows any stigmata of the disorder. The presence of ichthyosis suggests that there may be a metabolic component to this syndrome. In view of the consanguinity and pattern of the malformations, autosomal recessive inheritance seems likely.